THE IMPACT OF FUEL OIL RAISE IN FUEL OIL FISHERMAN INCOME TO PURSE SEINE VESSELS FISHING PORTS PROGRAM LANDED CATCH IN OCEAN (PPP) BUNGUS SUMATERA WEST SUMATRA WEST PROVINCE - Feby Yuranda; Zulkarnaini '; Hendrik ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in January 2016 for PPS Bungus West Sumatra Province to Changes in the area, duration and frequency of the arrests, operating expenses and income of fishermen owners and tenants vessel chart floating 60 GT and 90 GT with the fuel price hike diesel prices to be determined in this study Rp. 6400, - / liter and Rp. 6900, - / liter. The method used in this experiment is the case research method, the determination of the respondents a layered sample in this study.The study concludes that the increase in fuel prices has not led to changes in the fishing area (fishing grounds), Fishing journey (time of Fisheries), frequency, and timing. But the increase in fuel prices led to rising costs operasinal Purse ship saine 60 GT Rp 7.6766 million, - / trip (12.8%) and 90 GT vessel Purse Saine is Rp. 14.115 million, - / trip (11.6%). On the other hand, the increase in operating costs due to rising diesel prices led to a decline in the net income of each received - any fisherman. Fishing boats Stock Exchange Saine 60 GT decreased the average income of Rp. 7.6766 million, - / trip (2.5%) and 90 GT vessel saine wallet fell on average - an average of Rp. 14.115..000 .- / travel (2.8%).Keywords: impact of an increase, revenue, Purse Seine, FUEL